2020 FDA/EMA approvals for new immunotherapy drug technologies and applications - Maryam Monajati; Samira Sadat Abolmaali; Alimohammad Tamaddon (Shiraz University of Medical Sciences, 2021)
Immunotherapy is a new approach applied in treatment of infections, autoimmune diseases, or cancer by activating or suppressing the immune system. Pre-clinical and clinical investigations on discovering new products with high efficacy and low side effects are still ongoing. Clinical studies revealed numerous advantages of immunotherapy over chemotherapy, including prolonged progression-free survival and improved overall survival rate. However, immunotherapy may cause occasional severe adverse reactions due to an overactive immune system. This review gives an overview of new immunotherapeutic products approved by FDA/EMA in 2020. Moreover, the technologies used in manufacturing monoclonal antibodies (mAbs), antibody-drug conjugates (ADCs), and CAR-T cells are explained. In 2020, mAbs approved for the first time in management of migraine, autoimmune CNS disease, and thyroid eye disorder. In addition, new ADC and CAR-T cell therapeutics were authorized by FDA for mAb-targeted treatment of metastatic breast cancer and multiple myeloma, and mantle cell lymphoma, respectively. Despite the complexity and ambiguity of the technological development, ADCs and CAR-T cell therapy have great potential for further clinical applications in cancer therapy.